2016
DOI: 10.1002/phar.1760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracorporeal Membrane Oxygenation Use on Sedative Requirements in Patients with Severe Acute Respiratory Distress Syndrome

Abstract: Although the application of ECMO during severe ARDS resulted in a period of maximum sedation exposure that was both greater and took longer to reach, factors other than ECMO, particularly high-dose opioid administration, appeared more likely to account for this maximum sedation use. Further research surrounding sedative requirements, clearance, and patient response during ECMO is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 36 publications
1
58
0
Order By: Relevance
“…The authors found that the maximum median 6‐hour sedative exposure was nearly twice as high in the ECMO group and was reached nearly 3 days later when compared to the group not receiving ECMO. However, there was no significant difference in 6‐hour sedative exposure in adjusted analyses [23]. Therefore, this study challenges whether the increased requirements of opioids and sedatives are a result of circuit‐related factors alone or whether other factors, such as tolerance, age or pharmacogenomics, play a central role.…”
Section: Analgesia and Sedationmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors found that the maximum median 6‐hour sedative exposure was nearly twice as high in the ECMO group and was reached nearly 3 days later when compared to the group not receiving ECMO. However, there was no significant difference in 6‐hour sedative exposure in adjusted analyses [23]. Therefore, this study challenges whether the increased requirements of opioids and sedatives are a result of circuit‐related factors alone or whether other factors, such as tolerance, age or pharmacogenomics, play a central role.…”
Section: Analgesia and Sedationmentioning
confidence: 94%
“…The only comparative trial to date is a recent retrospective cohort study that enrolled consecutive adult patients with severe respiratory failure with ( n  = 34) or without ( n  = 60) venovenous ECMO support requiring at least one sedative to maintain a level of wakefulness appropriate to maintain patient comfort and safety while optimizing oxygenation and ventilator support [23]. The authors found that the maximum median 6‐hour sedative exposure was nearly twice as high in the ECMO group and was reached nearly 3 days later when compared to the group not receiving ECMO.…”
Section: Analgesia and Sedationmentioning
confidence: 99%
“…Secondary outcomes included cumulative doses and duration of other analgesic and sedative agents used, proportion of patients receiving multiple sedative agents, daily RASS score, delirium‐coma‐free days, mechanical ventilation‐free days, ICU and hospital length of stay, and hospital mortality. In addition, total sedation dose during the first 7 days following DCL was compared by converting all sedatives to midazolam equivalents (5 mg/hr midazolam = 200 mg/hr propofol = 74.1 μg/hr dexmedetomidine) …”
Section: Methodsmentioning
confidence: 99%
“…For instance, compared to ARDS patients who do not receive ECMO, patients receiving ECMO may need higher sedation to tolerate the invasiveness of the procedure, to compensate for sedatives consumed by the ECMO circuit itself, 37 and because patients who receive ECMO tend to be younger and have higher illness severity. 38,39 Whether higher sedation is actually necessary for these patients is not known.…”
Section: Minimizing Sedationmentioning
confidence: 99%